HUBUNGAN MOTIVASI DENGAN SIKAP WANITA USIA SUBUR (WUS) TERHADAP PEMANFAATAN PELAYANAN PAP SMEAR - Witari, Deni; Yuliandari, Ni Putu (Jurnal Genta Kebidanan, 2016)
Abstract : Relationship Motivasion with attitude about fertile woman on the use of health services in pap smear.Cervical cancer is the number one killer in Indonesia. Indonesia has created programs to prevent cervical cancer, among which pap smear aimed at finding cancer early stage and reduce the incidence of cervical cancer. The purpose of this study is to determine the relationship between motivation and attitude of women of childbearing age on the utilization of services in health centers III pap smear South Denpasar 2016. This research is an analytic correlation with cross sectional approach, conducted in Puskesmas III South Denpasar. The number of samples taken by accidental sampling technique, with the number of respondents as many as 40 respondents.The results of this research show the majority, or 23 respondents (57.5%) had low motivation and mostly or 21 respondents (52.5%) have a negative attitude. Based on the test data were analyzed using Spearman rank correlation test through SPSS computer assistance obtained rs 0.803 which lies between 0.80 to 1.00, which means the level of relationship is very strong and with a level of significance (p <0.05). In this study, p value = 0.000 <0.05, which means that there is a relationship between motivation and attitude of women of childbearing age on the utilization of the pap smear.Abstract : Hubungan Motivasi Dengan Sikap Wanita Usia Subur Terhadap Pemanfaatan Pelayanan Pap Smear. Kanker serviks merupakan pembunuh nomor satu di Indonesia. Indonesia telah dibuat program-program untuk mencegah kanker serviks, diantaranya yaitu pap smear yang bertujuanuntuk menemukan stadium kanker yang lebih awal dan menurunkan angka kejadian kanker serviks. Penelitian ini bertujuan untuk mengetahui hubungan antara motivasi dengan sikap wanita usia subur terhadap pemanfaatan pelayanan pap smear di Puskesmas III Denpasar Selatan. Penelitian ini merupakan penelitian analitik korelasi dengan pendekatan cross sectional, yang dilakukan di Puskesmas III Denpasar Selatan. Jumlah sampel diambil dengan teknik accidental sampling, dengan jumlah responden sebanyak 40 responden. Hasil penelitian ini menunjukkan sebagian besar atau 23 responden (57,5%) memiliki motivasi rendah dan sebagian besar atau 21 responden (52,5%) memiliki sikap yang negatif. Berdasarkan uji analisis data menggunakan uji korelasi rank spearman melalui bantuan komputer SPSS diperoleh rs 0,803 yang terletak antara 0,80-1,00 yang artinya tingkat hubungannya sangat kuat dan dengan tingkat signifikansi (p<0,05). Dalam penelitian ini p value = 0,000 <0,05 yang berarti ada hubungan antara motivasi dengan sikap wanita usia subur terhadap pemanfaatan pelayanan pap smear.